2014
DOI: 10.1136/bjophthalmol-2013-304786
|View full text |Cite
|
Sign up to set email alerts
|

First clinical results on the feasibility, quality and reproducibility of aberrometry-based intraoperative refraction during cataract surgery

Abstract: This is the first report addressing quality and reproducibility of WA in a large sample. IWA refraction in aphakia, for instance, appears to be reliable once stable and pressurised anterior chamber conditions are achieved. More efforts are required to improve the precision and quality of measurements before IWA can be used to guide the surgical refractive plan in cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…First, during surgery, the patient is in a supine position. In our previous study13 changing the posture from seated to supine led to cyclotorsion and apparently also to a myopic SE shift. Second, the lid speculum may be responsible for significant changes in cylinder power and axis depending on how much the patient squeezed 14.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…First, during surgery, the patient is in a supine position. In our previous study13 changing the posture from seated to supine led to cyclotorsion and apparently also to a myopic SE shift. Second, the lid speculum may be responsible for significant changes in cylinder power and axis depending on how much the patient squeezed 14.…”
Section: Discussionmentioning
confidence: 72%
“…When three measurements of intraoperative refraction (termed M5, M6 and M713) were possible, these data were assessed through difference means plots and are presented with their limits of agreements in figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ORA measurements were obtained after the cataract was removed, and the anterior chamber was inflated to normotensive level with a cohesive viscoelastic (Healon– Abbott Medical Optics, Santa Ana, CA, USA), as previous studies have indicated successful measurements in aphakia with the presence of viscoelastic. [ 6 7 ] This study was completed with the ORA before the more recent upgrade to VerifEye+™ Technology.…”
Section: Methodsmentioning
confidence: 99%
“… 1 2 3 Wavefront analysis has expanded beyond excimer ablation and has been applied to wavefront customized lenses, visual quality assessment after ocular and multiple ocular pathologies. 4 5 6 7 8 9 …”
Section: Introductionmentioning
confidence: 99%